Skeletal muscle vascular and metabolic control: impacts of exogenous vs. endogenous nitric oxide synthesis - Ferguson, Scott Kohman (Kansas State University, 2015)
The purpose of this dissertation is to expand our knowledge on the physiological effects of the ubiquitous signaling molecule nitric oxide (NO). Focus is given to the impacts of the nitrate (NO[subscript]3[superscript]-) nitrite (NO[subscript]2[superscript]-) NO pathway on skeletal muscle vascular and metabolic function during exercise. The NO[subscript]3[superscript]--NO[subscript]2[superscript]--NO pathway has garnered tremendous research interest due to its ability to upregulate NO bioavailability independently of NO synthase (NOS) function and thus impact the metabolic responses to exercise. Chapter 2 demonstrates that NO[subscript]3[superscript]- supplementation via beetroot juice (BR) augments the skeletal muscle vascular responses to exercise. Five days of BR supplementation resulted in a significantly higher skeletal muscle blood flow (BF) and vascular conductance (VC) during exercise when compared to control. The increases in BF and VC were preferentially directed to muscles and muscle portions comprised predominantly of fast twitch fibers. Furthermore, exercising blood [lactate] was reduced, suggesting improved metabolic control. In chapter 3, BR resulted in a slower fall in the microvascular PO[subscript]2 (PO[subscript]2[subscript]m[subscript]v, the soul driving force for blood myocyte O[subscript]2 flux) during the crucial rest-contraction transition thereby preserving the pressure head needed to move O[subscript]2 from the capillary into the myocyte. Chapter 4 examines the effects of BR on fast vs. slow twitch muscles in which BR raised the PO[subscript]2[subscript]m[subscript]v during the steady state of muscle contractions in fast but not slow twitch muscles, likely due to the lower PO[subscript]2[subscript]m[subscript]v at rest and throughout muscle contractions within these tissues. Chapter 5 investigates the effects of direct arterial NO[subscript]2[superscript]- infusion on skeletal muscle BF and VC during exercise in rats with NOS blockade via N[superscript]G-nitro-L arginine methyl ester. NO[subscript]2[superscript]- infusion restored MAP and VC to levels observed in healthy control animals (with intact NOS function) highlighting the potential for a NO[subscript]2[superscript]- based therapy to positively impact vascular function in those with compromised NOS function such that is evident in many prevalent diseases. These results provide crucial mechanistic insight into the improved exercise tolerance observed in humans following NO[subscript]3[superscript]- supplementation whilst also challenging our current understanding of NO’s role in physiology and pathophysiology.
Keywords: nitric oxide; Blood flow; Exercise; physiology; oxygen; Physiology (0719)